Transformative strategies for dengue outbreak management in Malaysian construction sites: a comprehensive approach - Ahmad Halmi, Nur Afrina Qistina; Abdul Rahman, Haliza (Human Resources Management Academic Research Society (HRMARS), 2024)
This paper explores transformative strategies for dengue outbreak management in Malaysian construction sites through a comprehensive approach. Analysing the background of dengue outbreaks, the study emphasizes adaptability and innovation. It discusses the evolution of strategies, including the successful implementation of the e-Dengue system, and identifies challenges within construction sites. The significance of a comprehensive approach is underscored in managing dengue cases, particularly among university students, and addressing cardiac implications. Current initiatives focus on vector control programs, integrating community mobilisation, and considering specific challenges in construction sites. The integrated dengue outbreak management policy aligns with national health goals, emphasizing coordination and legislative support. Technology plays a critical role, contributing to a healthier working environment and strengthening genotyping surveillance. Educational interventions, community participation, and addressing environmental changes are essential components of this holistic strategy. In conclusion, the paper synthesizes key findings and insights, offering implications for future dengue outbreak management. The transformative strategies outlined, including innovative technologies, community engagement, and adaptation to environmental changes, provide a foundation for effective dengue prevention in Malaysian construction sites.